Performance and Impact of a CLIA, Point-of-care Respiratory PCR Panel in a Pediatric Clinic. Issue 3 (March 2020) - Beal, Stacy G.; Posa, Molly; Gaffar, Maira; Reppucci, Jennifer; Mack, Jasmine A.; Gurka, Matthew J.; Rand, Kenneth; Houck, Herbert; Kelly, Maria N.
Abstract : Background: Laboratory-based respiratory polymerase chain reaction (PCR) panels are rarely used in outpatient pediatric practice due to prolonged turn-around times and cost of medical equipment. The BioFire FilmArray Respiratory Panel EZ (RP EZ) is a Clinical Laboratory Improvement Amendments–waived respiratory pathogen PCR panel which rapidly tests for 14 common respiratory organisms. The aim of this study was to identify the distribution of organisms seen in pediatric clinics and to determine if utilization of this point-of-care test improved disease management, while exploring impact on clinic workflow. Methods: From January 2018 through January 2019, when clinically appropriate, patients were tested by the RP EZ and/or antigen tests (Clinic A) or antigen test only (Clinic B). Residual samples from Clinic B antigen tests were frozen and later tested on the RP EZ for definitive pathogen identification. Patient data and prescription records were extracted from the electronic health record. Results: A total of 430 patients had RP EZ tests performed, and at least 1 organism was detected in 70.4% of patients. The most common organisms identified were human rhinovirus/enterovirus, influenza, and respiratory syncytial virus. Appropriate treatment occurred for 93.6% of patients when the RP EZ was performed (Clinic A) versus 87.9% of patients who had only antigen tests performed (Clinic B, P = 0.0445). Utilization of RP EZ testing also significantly reduced appointment duration time (48.0 versus 54.9 minutes, P = 0.0009). Three false-positive influenza B results were identified by antigen testing. Conclusions: A point-of-care PCR panel improved patient care by providing an accurate diagnosis and shortened appointment duration. Abstract : Supplemental Digital Content is available in the text.